A bidirectional relationship between physical activity and executive function in older adults - Daly, Michael; McMinn, David; Allan, Julia L. (Frontiers in Human Neuroscience, 2015)
Physically active lifestyles contribute to better executive function. However, it is unclear whether high levels of executive function lead people to be more active. This study uses a large sample and multi-wave data to identify whether a reciprocal association exists between physical activity and executive function. Participants were 4,555 older adults tracked across four waves of the English Longitudinal Study of Ageing. In each wave executive function was assessed using a verbal fluency test and a letter cancellation task and participants reported their physical activity levels. Fixed effects regressions showed that changes in executive function corresponded with changes in physical activity. In longitudinal multilevel models low levels of physical activity led to subsequent declines in executive function. Importantly, poor executive function predicted reductions in physical activity over time. This association was found to be approximately 50% larger in magnitude than the contribution of physical activity to changes in executive function. This is the first study to identify evidence for a robust bidirectional link between executive function and physical activity in a large sample of older adults tracked over time.